PADRÕES DE SONO DA DÍADE MÃE-BEBÊ PREMATURO E SUAS IMPLICAÇÕES NOS INDICADORES DE SAÚDE MENTAL MATERNA - Bieger, Joice Amanda Schwab (2022)
The birth of a child, especially premature, is a factor of change in several aspects of a woman's life, whether physical, social, economic and psychological. This is a delicate phenomenon that can give mothers the opportunity to experience psychological disorders such as anxiety and depression. This study sought to evaluate, by comparing pre and post tests, the impact of the standardized psychoeducational guidance on the change of the sleep pattern of mother-premature infant dyad from six to 24 months of corrected age and of the sleep on maternal mental health indicators. Therefore, an intervention research was carried out, almost-experimental, of an evaluative nature, with a month-long follow-up of two homogeneous groups (control group and intervention group) of mother-infant dyads, in a specialized care service, from May 2021 to January 2022, through information and communication technology. The protocol for the intervention group comprised verbal and written instructions via infographic in folder format, with details on adequate sleep routines and baby's sleep hygiene. For the control group, information was provided by other health professionals, standard routine of the service under study. The sample was obtained by convenience, considering an average effect size equivalent to 0.50, a type I error (α) equal to 0.05 and a two-tailed analysis power of 0.95, resulting in a sample of 54 mothers of premature babies, as indicated for the test t of dependent sample. Being composed of 52 sample units in pre-test, being 26 participants in the control group and 26 in the intervention group, the measurement instruments used were: Sociodemographic Questionnaire, Pittsburgh Sleep Quality Index (PSQI-BR) and Sleep Disorders Assessment, to check the mother's and baby's sleep quality, and the Self Resport Questionnarie (SQR-20) for verification of maternal mental health indicators. An analysis of socioeconomic variables was performed in relation to the scores obtained in each scale applied before and after the intervention to verify their influence on the sleep of the mother and baby and on maternal mental health. As a result, the control group showed a significant decrease in sleep time after the baby's birth, when it is compared to the intervention group, as dictated by the following data. It is noteworthy that the control group received only a simplified explanatory material, while the intervention group received an explanatory material in video format with a greater number of explanations on the topic of care for premature newborns. The average variation of sleep time of mothers in the control group decreased significantly (p < 0.0001; Table 1) by approximately 6.33 hours, while that of mothers in the intervention group increased by 0.25 hours, that is, in 15 minutes, showing the efficiency of the intervention performed. It could be noted that, in the control group, among older mothers, they lost fewer hours of sleep after the birth of their children. Younger mothers, on the other hand, have a greater reduction in the variation of sleep time (Figure 2), indicating a worsening in sleep quality. A different pattern was observed for the intervention group, in which practically no change was observed in the variation of post-intervention sleep time in relation to the age of the mothers. Statistical difference was also obtained in the average variation of the post-intervention sleep time when the interaction between the control and treatment groups, the children's birth weight and their birth order were evaluated (p = 0.0172; Table 1). It was checked that for babies weighing less than 2 kg, the birth order practically did not affect the variation of post and pre-intervention sleep time in any of the groups studied (control and intervention), 12 with a certain improvement in sleep time of mothers in the intervention group in relation to their last children. For babies weighing more than 2 kg, however, a decrease in sleep time was observed for mothers in the intervention group in relation to the order of children, that is, mothers who had their 4th child slept less after the intervention. As for the mothers in the control group, the opposite was observed, and in the last children, such mothers slept more (Figure 3). However, it is worth mentioning that despite an indication of worsening of sleep quality in mothers who received the intervention, and whose children weighed more than 2 kg, this reduction in sleep was approximately -2 hours, while mothers in the control group reached reduce more than 10 hours of sleep.